Group Socialization of Digital Games to Encourage Users' Autonomous Reading Behavior and Content Backtracking: Based on the Domestic Console Game “Black Myth: WUKONG” Known Outside of Fixed Circle - Chaochen WANG, Ayang QI, Xiaoqing XU, Linwei CUI (Nongye tushu qingbao xuebao)
[Purpose/Significance] Research on the behavioral stimulation of online social platform interactions triggered by IP-based games on users' active learning and reading, the social demands within gaming communities and their derivative reading-sharing interactions constitute dual intrinsic motivations that promote autonomous reading behaviors. Exploring new developmental directions for reading promotion through digital game dynamics and group-based social guidance provides broader research perspectives for innovative knowledge acquisition and pedagogical learning paradigms. [Method/Process] Based on the game "Black Myth: WUKONG" as the research background, we collected relevant comments and original texts from four social media platforms. Using the LDA model for topic classification of the effectively collected data, users who demonstrated marked behavioral tendencie towards book-related engagement and reading activities attributable to the "WUKONG" game experience were manually identified from the aforementioned dataset. We explored the details of their social discourse and the behavior of user accounts through user-account backtracking, studying the factors that stimulate users' interest in reading and active reading behavior. [Results/Conclusions] Analysis of the five thematic clusters identified by the LDA modeling revealed that in the user behaviors focused on the theme of cultural exploration, 38.3% of the user behavior data showed increased exploratory engagement with original literary works and related content during "WUKONG" mediated group interactions. Whether this interactive exploration closely connects to reading habits needs further study. Further research has shown that a portion of users were influenced in their subsequent behaviors by this game and social interaction. Through text mining of user content on key topics, analysis revealed that 61.15% of user accounts had no prior engagement history, representing first-time participants in the cultural learning interactions of the "WUKONG" game. Notably, 23.7% of this cohort spontaneously expressed self-directed reading intentions during the game-social scenario. As the dominant subgroup in the dataset, their behavioral patterns suggest that gamified social platforms may serve as critical trigger mechanisms. It was found that the factors that stimulate users to read independently include competing for the right to speak in social interactions and obtaining gaming experiences. Accordingly, strategic practices for autonomous reading should accordingly be implemented through digital content guides, transmedia narrative interactions, and visual scene experiences. This research investigates the orienting mechanisms of digital games and community interactions in edutainment convergence, demonstrating both theoretical value and practical implications for user behavior analysis and reading promotion. While the study design ensured breadth of data collection, the heterogeneity of social attributes across platforms warrants further investigation. Subsequent studies should conduct platform-specific comparative experiments to strengthen the empirical foundation for behavioral intervention strategies.